Applying Human Rights and Reducing Coercion in Psychiatry following Service User-Led Education: A Qualitative Study - Susanna Every-Palmer; Leah Kininmonth; Giles Newton-Howes; Sarah Gordon (Harvard FXB Center for Health and Human Rights, 2020)
Despite the imperatives to reduce coercive practices such as substitute decision-making, seclusion, and restraint, the psychiatric profession has struggled to realize these aspirations. Education delivered by people with lived experience of mental distress can help facilitate change. We introduced a service user-led academic program for psychiatry residents focused on promoting human rights and reducing coercive practices in mental health care. Few published reports of such service user-led education exist. In this qualitative study, we analyze data exploring this new program's impact in practice. Four major themes were identified. Service user-led training was challenging but highly valued and prompted a paradigm shift, changing residents' thinking. Residents had so much promise in their early intentions to reduce coercive practices. However, numerous barriers impeded them from implementing these intentions. Power differentials that existed at multiple levels caused residents to experience themselves as "pawns" playing set roles working under a system with entrenched hierarchies, resource limitations, legislative frameworks, and public expectations operating to maintain the status quo. The apprenticeship model under which psychiatry residents work is a significant socializing influence. If only the "old paradigm" is modeled and taught, then this hinders more progressive thinking. Service user-led education should be offered more broadly.